Mode Calculation and Testing of a Car Body in White - Ying Yang; Guangyao Zhao; Dongbo Ma; Xiaobin Xu (Shock and Vibration)
The dynamic parameters of a car body in white (BIW) are important during a new car developing. Based on the finite element method, the model of a BIW is developed in which the welding points are treated specially as a new element type and the vibration modes of it are calculated. In modal testing, a fixed sine-sweeping exciter is used to conduct a single-point input force for the structure, whereas the output responses are picked up at different points to identify modes. The obtained modes are coincided both with the FE results and the practical testing.